Synergistic interactions between lecithin and fruit wax in oleogel formation. Issue 3 (6th March 2018) - Okuro, Paula K.; Tavernier, Iris; Bin Sintang, Mohd D.; Skirtach, Andre G.; Vicente, António A.; Dewettinck, Koen; Cunha, Rosiane L.
Abstract : Lecithin addition affected crystallization and gelation of fruit wax-based oleogels with sunflower oil. Abstract : In this study, the effect of lecithin (LEC) on the crystallization and gelation of fruit wax (FW) with sunflower oil was researched. A synergistic effect on the gel strength was observed at FW : LEC ratios of 75 : 25 and 50 : 50, compared to the corresponding single component formulations (100 : 0 and 0 : 100). Even below the critical gelling concentration ( C g ) of FW, the addition of lecithin enabled gel formation. Lecithin affected the thermal behavior of the structure by delaying both crystallization and gel formation. The phospholipid acted as a crystal habit modifier changing the microstructure of the oleogel, as was observed by polarized light microscopy. Cryo-scanning electron microscopy revealed a similar platelet-like arrangement for both FW as a single oleogelator and FW in combination with LEC. However, a denser structure could be observed in the FW : LEC oleogelator mixture. Both the oil-binding capacity and the thixotropic recovery were enhanced upon lecithin addition. These improvements were attributed to the hydrogen bonding between FW and LEC, as suggested by Raman spectroscopy. We hypothesized that lecithin alters the molecular assembly properties of the FW due to the interactions between the polar moieties of the oleogelators, which consequently impacts the hydrophobic tail (re)arrangement in gelator–gelator and solvent–gelator interactions. The lipid crystal engineering approach followed here offered prospects of obtaining harder self-standing structures at a lower oleogelator concentration. These synergistic interactions provide an opportunity to reduce the wax concentration and, as such, the waxy mouthfeel without compromising the oleogel properties.